Beyond Databases, Architectures and Structures. Advanced Technologies for Data Mining and Knowledge Discovery 12th International Conference, BDAS 2016, Ustroń, Poland, May 31 - June 3, 2016, Proceedings - Kozielski, Stanisław; Mrozek, Dariusz; Kasprowski, Paweł; Małysiak-Mrozek, Bożena; Kostrzewa, Daniel (Communications in Computer and Information Science,, 2016)
This book constitutes the refereed proceedings of the 12th International Conference entitled Beyond Databases, Architectures and Structures, BDAS 2016, held in Ustroń, Poland, in May/June 2016. It consists of 57 carefully reviewed papers selected from 152 submissions. The papers are organized in topical sections, namely artificial intelligence, data mining and knowledge discovery; architectures, structures and algorithms for efficient data processing; data warehousing and OLAP; natural language processing, ontologies and semantic Web; bioinformatics and biomedical data analysis; data processing tools; novel applications of database systems.